Vocational Education: An Instrument for Achieving the Seven-Point Agenda in Nigeria - Ogundiran, Samuel Ogunwale (NIU Journal of Social Sciences, 2018)
Nigeria government's 7-Point Agenda focuses on power and energy, food security and agriculture, wealth creation and employment, mass transportation, land reforms plus qualitative and functional education which are the needs to be met in the year 2020. The detailed objectives of the 7-Point Agenda are subsumed in the objectives of vocational and technical education which are considered an instrument for the achievement of the Agenda for national development. Vocational and technical education is capable of training more than the required manpower for Agenda reforms because it covers over one thousand careers which are germane to the national vision. The timing for mission accomplishment appears to be one of the problems facing the efforts. Furthermore, vocational and technical education with its impressive potentials for enhancing reforms in the nation's problem areas faces a lot challenges as explained in the paper. If Nigeria must be a truly industrialized nation, it has to integrate technology in all its ramifications into her culture because the technological development is culture-based.